Performance-based design of asphalt mixtures and review of key parameters. (5th March 2018) - Zaumanis, M.; Poulikakos, L.D.; Partl, M.N.
Highlights: Performance-based design of asphalt mixes can increase cost effectiveness, improve durability, reduce environmental impact. Matrix of 102 performance indicators will allow mix designer to reduce testing time and improve durability of pavements. Aging should be introduced as part of mixture design procedure for performance-based test methods. Graphical abstract: Image 1 Abstract: High content recycling, warm mix asphalt, and other advanced technologies are changing asphalt mixtures beyond the narrow margins where conventional volumetric asphalt mix design holds true. Performance-based tests can be used to characterize asphalt mixtures regardless of materials and technologies in use, thus allowing the extension of pavement life cycle, cost savings and minimization of environmental footprint. This article proposes a potential road map for implementation of performance-based tests as part of mix design procedures. Through an extensive literature review the effects of properties and proportions of binder, aggregates, modifiers and selected advanced technologies on key mixture performance-based parameters like cracking, rutting, stiffness, workability and moisture resistance are systematically summarized. A table indicating the expected performance-based test result trends is provided to aid in optimization of mixture composition. The information is intended to be the first source for a mix designer when deciding on means to improve performance or troubleshoot the failures of an asphalt mixture.